Development of Javanese Script Learning Media Based on Uno Stacko Game and Penta Helix Approach at SDN 2 Sidowarno - Bagus Prayoga; Harnanda Mita Anggar Sari; Luluk Sri Javita Asharani (Javanologi: International Journal of Javanese Studies, 2023)
The fading of Javanese culture and the literacy crisis are complex problems that have a further impact on the world of education on elementary school students in Javanese script literacy in a multicultural country like Indonesia. Factors that influence the lack of Javanese script literacy are learning media that are less attractive and limited. In realizing Education for Sustainable Development (ESD), one of the efforts to preserve and introduce Javanese script to support Indonesia gold 2045 can use gaming learning media. Empowerment of the Javanese script can be implemented through the role of education staff in learning based on the uno stacko game and the penta helix system. The purpose of this study was to determine the feasibility of learning media based on the uno stacko game and the penta helix approach at SD N 2 Sidowarno and to determine student responses to the feasibility of learning media based on the uno stacko game and the penta helix approach. This research uses the research and development (R&D) method with the Borg & Gall model. Data were obtained from teacher questionnaires and student responses, validation questionnaires from subject matter experts, media experts, and also interviews. The results of the expert assessment were 87.45% for subject matter experts, 85.84% for media experts, and 87.77% for educators, while the student response was 82.43%. From the research results it is known that learning Javanese script using the Uno Stacko game can increase student learning motivation and form effective learning. In addition, based on assessments from material experts, media experts, and teachers as well as responses from students, it can be concluded that the Javanese script learning media based on the uno stacko game and the penta helix approach are suitable for use as learning media. In addition, based on the research results, it can be seen that the existence of a penta helix collaboration system can be an effective effort in supporting Education for Sustainable Development (ESD).Keywords: Javanese Script, uno stacko game, penta helix